3D‐Printed Wood‐Fiber Reinforced Architected Cellular Composites. Issue 11 (6th August 2020) - Estakhrianhaghighi, Ehsan; Mirabolghasemi, Armin; Zhang, Yingnan; Lessard, Larry; Akbarzadeh, Abdolhamid
Abstract : Enhancing thermomechanical properties of bio‐based polymers by the introduction of cellulose‐based compounds not only paves the way for developing sustainable materials but also opens new opportunities in low‐cost additive manufacturing. Herein, a novel accessible methodology is provided for integrating waste wood fibers, a versatile renewable resource of cellulose, into polylactic acid (PLA) polymers to produce sustainable wood‐fiber reinforced PLA (WF‐PLA) filaments and then to 3D print high‐performance architected cellular composites. The experimental results demonstrate increased stiffness (18%), ultimate strength (9%), fracture strain (15%), toughness (44%), thermal conductivity (23%), and reduced overall density (10%) for 3D‐printed composite dogbones made of optimum wood‐fiber contents, compared with the PLA counterpart. Following the growing interest in architected cellular solids, a rising class of advanced materials with superior multifunctional properties, WF‐PLA filaments are used to 3D print two quasi‐isotropic cellular materials, hexagonal and novel mixed square ("isomixed") microarchitectures. The WF‐PLA isomixed cell exhibits considerably enhanced stiffness (91%) and ultimate strength (48%) compared with the PLA hexagonal honeycombs. The WF‐PLA architected composites offer a first‐of‐a‐kind strategy to additively manufacture sustainable advanced materials with enhanced thermomechanical properties out of low‐cost waste materials through an optimized material composition and the rational design of underlying microarchitectures. Abstract : It is shown that using wood‐fiber reinforced polylactic acid (PLA) composite filaments to 3D print cellular materials is a promising approach to not only extend the material properties of the widely used PLA biopolymer, which has inherent weaknesses associated with its brittleness but to also offer a new class of sustainable lightweight advanced materials with enhanced structural properties.